IMPLEMENTASI KEGIATAN EKSTRAKURIKULER PRAMUKA DALAM MEMBENTUK KARAKTER DISIPLIN SISWA DI SEKOLAH DASAR - Darwanti, Asri; Sutama, Sutama; Achmad Fathoni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explore how the implementation of scout extracurricular activities at SDN 02 Ngadiluwih can serve as an effective medium for shaping students' disciplinary character. The research employs a descriptive qualitative approach. The subjects of the study consist of 4th, 5th, and 6th-grade students actively participating in scout extracurricular activities, scout instructors, and parents of students at SDN 02 Ngadiluwih, Matesih, Karanganyar. Data were collected through in-depth interviews, participatory observation, and documentation. The qualitative data collected were analyzed using a thematic approach. The results of the study show that shaping disciplinary character through scout activities involves several effective approaches. Instructors or coaches use various strategies, including habitualization, role modeling, task assignments, advice, and consistent and fair reward and punishment. The development of independence skills is also a key focus in scout activities, where students are taught to be self-reliant in completing tasks and facing challenges. Additionally, regular reflection and evaluation provide students with the opportunity to understand and internalize disciplinary values in their daily lives. Through this approach, scout activities not only shape students' disciplinary character but also prepare them to be responsible and disciplined in facing various situations in life.